Feasibility and acceptability of a 12-week advanced hip-focused exercise intervention program for female athletes - Dischiavi, S. L.; Wright, A. A.; Bleakley, C. M. (Journal of Science in Sport and Exercise, 2025)
Purpose Anterior cruciate ligament (ACL) injuries and patellofemoral pain (PFP) continue to show high incidence rates, and poor long term outcomes. Key exercise elements were synthesized into an advanced hip focused exercise strategy and were administered to a sample of female athletes. This study examined the feasibility and impact of a 12-week advanced hip muscle strengthening program on physical performance measures and peak hip muscle torques.